Prognostic value of changes in arterial stiffness in men with coronary artery disease - Iana A Orlova; Eradzh Yu Nuraliev; Elena B Yarovaya; et al (Vascular Health and Risk Management, 2010)
Iana A Orlova, Eradzh Yu Nuraliev, Elena B Yarovaya, Fail T AgeevOutpatient department, Russian Cardiology Research Center, Moscow, Russian Federation Background: Men with coronary artery disease (CAD) have been shown to have enhanced arterial stiffness. Arterial function may change over time according to treatment, but the prognostic value of these changes has not been investigated.Objectives: The aim of the present study was to assess whether an improvement in large artery rigidity in response to treatment, could predict a more favorable prognosis in a population of men with CAD.Methods: A total of 161 men with CAD (mean age 56.8 ± 10.9 years) being treated with conventional therapy underwent brachial-ankle pulse wave velocity (PWVba) measurements at baseline and after six months. Follow-up period was 3.5 years. End-points were major adverse cardiac events (MACE): acute myocardial infarction, unstable angina, coronary intervention, or cardiac death.Results: During the three-year follow-up period (since initial six-month follow-up), 30 patients experienced MACE. After six-month follow-up, PWVba had not improved (∆PWVba ≥ 0%, relative to baseline) in 85 (52.8%) of 161 men (Group 1), whereas it had improved (∆PWVba < 0%) in the remaining 76 men (47.2%) (Group 2). During follow-up, we noticed 24 cardiovascular events in Group 1 and six events in Group 2 (P < 0.001). Cox proportional hazards analyses demonstrated that independent of conventional risk factor changes, absence of PWVba decrease was a predictor of MACE (RR 3.99; 95% CI:1.81–8.78; P = 0.004). The sensitivity of ∆PWVba was 80% and its specificity was 54%.Conclusions: This study demonstrates that an improvement in arterial stiffness may be obtained after six months of conventional therapy and clearly identifies patients who have a more favorable prognosis.Keywords: arterial stiffness, coronary artery disease, prognosis